Participatory, art-based appreciative inquiry with artists labelled/with intellectual and developmental disabilities. (1st March 2022) - Miller, Sara
People labelled/with intellectual and developmental disabilities (IDD) participate in community-based studio programming across the United States, yet their experiences and preferences for studio programming are not well known. The goal of this research was to learn what artists in a community-based studio think is important about their studio and what they want to change in the future. Using art-based appreciative inquiry and online methods, the artists were prompted to talk and create artwork about 'what is most important' in the studio and 'what we want for the future'. The artists reported that the most important aspects of the studio are the staff and their friends at the studio and the opportunity to make art that is motivated by their interests. The wishes expressed by the artists included increased opportunities to be social, to make more money, to have more community access and more choice and control in the studio.